Comparison of conventional percutaneous nephrolithotomy versus endoscopic combined intrarenal surgery in complex renal calculus – Our institutional experience - Rajasekar Maruthamuthu,; Jayaprakash Narashimman,; Mahendran Ganesamoorthy,; Thiruvarul PV,; Prasad Sivasamy, (Asian Journal of Medical Sciences, 2024)
Background: Complex renal calculi, characterized by their size, location, and composition, pose a significant challenge to urologists due to the potential for complications and the difficulty in achieving complete stone clearance. Conventional percutaneous nephrolithotomy (PCNL) and endoscopic combined intrarenal surgery (ECIRS) are two established techniques for managing these complex renal calculi. Aims and Objectives: The aims and objectives are to compare the effectiveness, safety, and outcomes of PCNL versus ECIRS in managing complex renal calculi in a cohort of 60 cases treated at GMKMCH-Salem. Materials and Methods: A retrospective analysis was conducted on 60 patients with complex renal calculi who underwent either conventional PCNL or ECIRS during a specified period at GMKMCH-Salem. Patient demographics, stone characteristics, procedural details, intraoperative and post-operative parameters, and complications were analyzed and compared between the two treatment groups. Results: The study found that both PCNL and ECIRS techniques were effective in treating complex renal calculi. However, significant differences were observed between the two groups in terms of outcomes. The ECIRS technique exhibited superior outcomes with higher stone clearance rates (P<0.001), shorter operative times (P<0.05), and reduced hospital stays (P<0.05) compared to conventional PCNL. Conclusion: This study demonstrates that ECIRS is a promising alternative to conventional PCNL in the management of complex renal calculi. The ECIRS technique yielded higher stone clearance rates, shorter operative times, and reduced hospital stays, potentially improving patient outcomes and reducing health-care costs. Although our findings show favorable results for ECIRS, the decision between conventional PCNL and ECIRS should be based on individual patient characteristics, surgeon expertise, and resource availability.